Draft Genome Sequences of Two Ulvan-Degrading Isolates, Strains LTR and LOR, That Belong to the Alteromonas Genus - Kopel, Moran (American Society for Microbiology, 2014)
Here, we report the draft genome sequence of two ulvan-degrading Alteromonas spp. isolated from the feces of the sea slug, Aplysia. These sequenced genomes display a unique ulvan degradation machinery compared with ulvanolytic enzymes previously identified in Nonlabens ulvanivorans.